Development of a supercritical CO2 decellularization technology - Loczenski, Rabea (2020)
Decellularization of mammalian tissue describes the process by which cellular materials are removed from the extracellular matrix (ECM, Hinderer, Layland and Schenke-Layland, 2016). Current decellularization methodologies utilise a multitude of decellularization agents, such as detergents, solvents and biological enzymes, to achieve successful decellularization, which has been demonstrated with a number of different organs (i.e. heart (Ott et al., 2008), lung (Petersen et al., 2012), kidney (Song et al., 2013) and liver (Uygun et al., 2010; Mazza et al., 2015)). However, the use of these common decellularization agents causes damage to the derived ECM ultrastructure. Furthermore, these agents are often retained within the tissue following the decellularization process (Faulk et al., 2014; White et al., 2016), which may negatively impact potential downstream application.